2016
DOI: 10.1097/imi.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Complete Obliteration of the Left Atrial Appendage an Analysis of Epicardial Excision and Novel Pericardial Patch Exclusion

Abstract: Objective Conventional epicardial excision is believed to be the most effective method of surgically obliterating the left atrial appendage (LAA), although incomplete resection and residual LAA volume may undermine its effectiveness. We sought to compare the impact of conventional epicardial excision with a novel LAA pericardial patch exclusion on residual LAA volume. Methods We performed LAA obliteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…2 However, some researchers have also found that surgical closure of the LAA, especially with sutures, has a potentially higher risk of thromboembolism if the LAA reopens. 3 4 Some surgeons have performed a pericardial patch exclusion (PPE) technique to close the LAA in cadavers using autologous pericardial pieces 5 . However, there is still a lack of clinical results on the use of this technique in humans, so its e cacy and safety have not been fully evaluated clinically.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, some researchers have also found that surgical closure of the LAA, especially with sutures, has a potentially higher risk of thromboembolism if the LAA reopens. 3 4 Some surgeons have performed a pericardial patch exclusion (PPE) technique to close the LAA in cadavers using autologous pericardial pieces 5 . However, there is still a lack of clinical results on the use of this technique in humans, so its e cacy and safety have not been fully evaluated clinically.…”
Section: Introductionmentioning
confidence: 99%